Social inequality in sexual and reproductive health in Ecuador: an analysis of gaps by levels of provincial poverty 2009-2015 - Juan Pablo Gutiérrez; René Leyva Flores; Belkis Aracena Genao (BMC, 2019)
Abstract Background Adequate access to sexual and reproductive health services is associated with better results. Analyzing the differences in access and outcomes of sexual and reproductive health (SRH) by share of poverty at the regional level makes it possible to measure the magnitude of the challenge of inequity. This paper aims to estimate the magnitude of health inequality in SRH in Ecuador for the period 2009-2015. Methods This study analyzed health inequalities in sexual and reproductive health indicators (obstetric and abortion complications, caesarean and home deliveries, adolescent fertility, and maternal mortality) for 2009 and 2015 comparing provinces in Ecuador. The absolute and relative gaps were estimated between provinces grouped by the percentage of individuals in multidimensional poverty; the slope index of inequality and the relative index of inequality were estimated as measures of gradient; and finally, the concentration index was also estimated. Results The analysis identified that obstetric complications, abortion complications, and cesareans have tended to increase from 2009 to 2015, without relevant differences between provinces ordered by poverty. Adolescent fertility decreased in the country as well as the inequality in its distribution among provinces: the CI was − 0.046 in 2015, down from − 0.084 in 2009. Home deliveries as a ratio of total deliveries have a decreasing trend with mixed results in terms of inequality: while there is a decrease in the absolute gap from − 211.06 to 184.4 between 2009 and 2015, the concentration index increased from − 0.331 to − 0.496. Finally, the maternal mortality rate increased in the period, also with greater inequality: from an absolute gap of − 39.30 in 2019, up to − 46.7 in 2015. In the same direction, the CI went from − 0.127 to − 0.174. Conclusions Ecuador faces major challenges in terms of both levels and inequalities in SRH outcomes and access to services. These inequalities related to poverty highlight the persistence of social inequities in the country. These health inequalities affect the wellbeing of Ecuadorian women but they are amendable. There is a need for pro-equity interventions, with stronger efforts in areas (provinces) with larger socioeconomic vulnerabilities.